Linear ubiquitination-mediated NF- B regulation and its related disorders - Fuminori Tokunaga (2013)
Ubiquitination is a post-translational modification involved in the regulation of a broad variety of cellular functions, such as protein degradation and signal transduction, including nuclear factor-κB (NF-κB) signalling. NF-κB is crucial for inflammatory and immune responses, and aberrant NF-κB signalling is implicated in multiple disorders. We found that linear ubiquitin chain assembly complex (LUBAC), composed of HOIL-1L, HOIP and SHARPIN, generates a novel type of Met1 (M1)-linked linear polyubiquitin chain and specifically regulates the canonical NF-κB pathway. Moreover, specific deubiquitinases, such as CYLD, A20 (TNFAIP3) and OTULIN/gumby, inhibit LUBAC-induced NF-κB activation by different molecular mechanisms, and several M1-linked ubiquitin-specific binding domains have been structurally defined. LUBAC and these linear ubiquitination-regulating factors contribute to immune and inflammatory processes and apoptosis. Functional impairments of these factors are correlated with multiple disorders, including autoinflammation, immunodeficiencies, dermatitis, B-cell lymphomas and Parkinson's disease. This review summarizes the molecular basis and the pathophysiological implications of the linear ubiquitination-mediated NF-κB activation pathway regulation by LUBAC.